Intraspecific competition between Amaranthus hybridus L. and A. viridis L. - Maluf, Angela Maria (Pesquisa Agropecuaria Brasileira, 1999)
Intraspecific competition trials were carried out for Amaranthus viridis L. and A. hybridus L., the latter species with two distinct biotypes, a green and a purple type. Three independent trials were made, with five different seed densities per pot for each species or biotype. In general terms, seeds that germinated promptly were responsible for the formation of the next generation, these early seedlings being more competitive. The carrying capacity was reached with 20 seeds per pot, no increase in the number of adult plants observed by increasing the seed density. This shows that the environmental suporting capacity, not the size of the seed bank in the soil, regulates the population size. A similar conclusion holds true for dry matter yield. Under competition, the species A. hybridus - green biotype and A. viridis produced larger biomass for reproductive structures (22% to 34%) than A. hybridus - purple biotype (15% to 18%), the former species being therefore better r-strategists than the latter.